Assessing neuromuscular system via patellar tendon reflex analysis using EMG in healthy individuals - Zakia Khatun; Zakia Khatun; Sara Kristinsdóttir; Arndís Thóra Thórisdóttir; Linda Björk Halldórsdóttir; Francesco Tortorella; Paolo Gargiulo; Paolo Gargiulo; Thordur Helgason; Thordur Helgason (Frontiers in Neurology)
Patellar tendon reflex tests are essential for evaluating neuromuscular function and identifying abnormalities in nerve conduction and muscle response. This study explored how age, height, weight, and gender influence reflex response times in healthy individuals, providing a reference for future research on different neuromuscular conditions. We analyzed reflex onset, endpoint, and total duration of reflexes using electromyography (EMG) recordings from 40 healthy participants. Reflexes were elicited by striking the patellar tendon, and participants were grouped based on age, height, weight, and gender. We investigated both the individual and combined effects of these factors on reflex response times. Additionally, height and weight-normalized data were analyzed to clarify their roles in influencing reflexes across age groups. Gender-specific analyses were conducted as well to assess potential differences between males and females. Our findings indicated that reflex onset was significantly delayed in elderly individuals, particularly in taller and heavier individuals, and in males compared to females. Even with height normalization, elderly participants showed slower reflexes. Weight-normalized data revealed that younger participants exhibited longer total reflex durations, likely due to their greater height, which impacted nerve conduction time. This trend was consistent across genders, with males generally exhibiting longer duration of reflex response times. These findings provide insights into how different demographic factors, particularly aging, affect neuromuscular reflexes and could serve as a reference for diagnosing and monitoring neuromuscular disorders.